Analysis of Social System Innovation in Digital Transformation of Kotakmedia Indonesia: The Perspective of Innovation Diffusion Theory - Hanugrah Nur Muharrani Putri; Filosa Gita Sukmono (Jogjakarta Communication Conference (JCC), 2025)
In the context of digital transformation, the role of social systems is becoming increasingly significant as technological change often requires cross-functional collaboration, cultural adaptation and managing resistance to change. However, many organizations face challenges in managing their social systems during the digital transformation process. This research aims to explore how the social system in Kotakmedia Indonesia plays a role in the process of adopting innovations that occur in a structured manner during its digital transformation. The method used in this research is a case study with a qualitative approach. The informants in this study used purposive sampling technique with data collection techniques using in-depth interviews and observations. The results showed that the success of innovation adoption depends on interactions between individuals and organizational collaboration. In the innovation diffusion process, the role of opinion leaders and internal communication mechanisms contribute to the acceleration of innovation adoption. An organizational structure that supports innovation diffusion allows innovation adoption to run more systematically. Innovators and early adopters act as the main motors of innovation, while the majority group tends to follow after seeing initial success. In the context of the social system, factors such as social structure, system norms, the role of leaders, and change agents are interconnected in determining the success of innovation adoption at Kotakmedia Indonesia.